Infant body composition assessment in the neonatal intensive care unit (NICU) using air displacement plethysmography: Strategies for implementation into clinical workflow. (June 2021) - Alja'nini, Zaineh; McNelis, Kera Michelle; Viswanathan, Sreekanth; Goddard, Gillian R.; Merlino-Barr, Stephanie; Collin, Marc; Groh-Wargo, Sharon
Summary: Nutritional management is integral to infant care in the neonatal intensive care unit (NICU). Recent research on body composition that specifically evaluated fat and fat-free mass has improved our understanding of infant growth and nutritional requirements. The need for body composition monitoring in infants is increasingly recognized as changes in fat mass and fat-free mass associated with early growth can impact clinical outcomes. With the availability of air displacement plethysmography (ADP) as a noninvasive method for assessing infant body composition and published normative gestational age- and sex-specific body composition curves, it is justifiable to integrate this innovation into routine clinical care. Here we describe our experiences in implementing body composition measurement using ADP in routine clinical care in different NICU settings.